Zakat and Its Role in Reducing Economic Inequality in Indonesia - Ghazy Triyatno; Saffanah Az Zahra (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2026)
This research investigates the potential of zakat in reducing economic inequality in Indonesia through a meta-analysis approach. Economic inequality remains a major challenge in achieving social justice, and Zakat is viewed as a potential instrument for income redistribution. This research approach uses meta-analysis to identify trends, insights, and gaps in the literature. As a result of this research, Zakat has proven to contribute significantly to reducing economic inequality by improving the welfare of poor community groups (mustahiq). However, this effectiveness depends on the transparent, accountable, and data-driven governance of Zakat. This research recommends strengthening collaboration between Zakat institutions, the government, and the community to enhance the coverage and impact of zakat distribution. These findings support zakat as an important instrument in sustainably addressing economic inequality.